Intravenous Tissue Plasminogen Activator for an Ischemic Stroke with Occult Double Primary Cancer - Yoneda, Yukihiro (Case Rep Neurol, 2014)
BACKGROUND: In patients with advanced-stage cancer, systemic thrombolysis with tissue plasminogen activator (tPA) for hyperacute ischemic stroke is not strictly off-label, but it is at higher risk of complications (including bleeding). CASE REPORT: A 71-year-old male with unrecognizable malignancy developed a hemispheric ischemic stroke and received intra-venous tPA within 4.5 h of onset, followed by anticoagulation treatment after 24 h of throm-bolysis. Two days later, the patient had tarry stool and progressive anemia, receiving a blood transfusion. The systemic workup documented the presence of double primary cancers with advanced stage gastric and rectal cancers, and the patient subsequently received palliative care. The outcome at 3 months was a modified Rankin Scale of 5, and the patient died 6 months after the stroke. DISCUSSION: Although systemic thrombolysis with tPA for ischemic stroke in patients with advanced-stage cancer may be performed relatively safely, optimal post-thrombolysis management is important to prevent the complications.